2023
DOI: 10.1037/pha0000637
|View full text |Cite
|
Sign up to set email alerts
|

Using alcohol biosensors and biomarkers to measure changes in drinking: Associations between transdermal alcohol concentration, phosphatidylethanol, and self-report in a contingency management study of persons with and without HIV.

Abstract: Alcohol use can be measured in many ways, including objectively through transdermal alcohol biosensors (e.g., transdermal alcohol concentration; TAC) or blood biomarkers (e.g., phosphatidylethanol; PEth), or subjectively through self-report (e.g., with the timeline followback; TLFB). However, it is unclear which measures best indicate changes in alcohol use within individuals following intervention, and if they have concurrent validity. In the context of contingency management (CM) with a goal of 30-day abstin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Data were downloaded from the server through a password-protected portal. The Transdermal Alcohol Sensor Data Macro (TASMAC Software) read and interpreted data from the SCRAM” ( 62 ). The participant took the DirectConnect device home so that the research assistant could check their daily data.…”
Section: Methodsmentioning
confidence: 99%
“…Data were downloaded from the server through a password-protected portal. The Transdermal Alcohol Sensor Data Macro (TASMAC Software) read and interpreted data from the SCRAM” ( 62 ). The participant took the DirectConnect device home so that the research assistant could check their daily data.…”
Section: Methodsmentioning
confidence: 99%
“…This software is capable of processing whole cohorts of data, advancing the ability for researchers to efficiently identify alcohol consumption in participants' natural environment. Future directions include training models to predict device removal, drinking intensity, or breath alcohol concentration, examining whether demographics or other biomarkers contribute to model accuracy (Richards et al, 2023), and continuing to validate the present models with TAC data from diverse environments and samples.…”
Section: Figurementioning
confidence: 99%
“…The implementation of this is not feasible with staff time and resources and multiple daily visits would increase the burden on both patients and staff, as well as being potentially invasive. However, with the development of TAS, there is now the possibility to objectively monitor alcohol consumption 24/7 without these barriers [19,20,[41][42][43][44][45][46].…”
Section: Original Manuscriptmentioning
confidence: 99%
“…Previous literature has started to explore TAS use to implement CM [19,20,[41][42][43][44][45][46]. These studies found TAS successful in implementing the CM procedure and found that the CM intervention was able to significantly reduce alcohol consumption [19,20,42,43].…”
Section: Original Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation